Experiences and Perceptions of Telephone-delivery of the Common Elements Treatment Approach for Mental Health Needs Among Young People in Zambia During the COVID-19 Pandemic - Munthali-Mulemba, Saphira; Figge, Caleb J.; Metz, Kristina; Kane, Jeremy C.; Skavenski, Stephanie; Mwenge, Mwamba; Kohrt, Brandon A.; Pedersen, Gloria A.; Sikazwe, Izukanji; Murray, Laura K. (Frontiers in Public Health, 2022)
Abstract Background: Mental and behavioral health needs are immense in low-to-middle income countries (LMIC), particularly for adolescents and young adults (AYA). However, access to mental health services is limited in LMIC due to barriers such as distance to a health care site, low number of providers, and other structural and logistical challenges. During the COVID-19 pandemic, these barriers were significantly exacerbated and, thus, mental health services were severely disrupted. A potential solution to some of these barriers is remote delivery of such services via technology. Exploration of AYA experiences is needed to understand the benefits and challenges when shifting to remotely delivered services. Methods: Participants included 16 AYA (15-29 years) residing in Lusaka, Zambia who met criteria for a mental or behavioral health concern and received telehealth delivery of the Common Elements Treatment Approach (CETA). AYA participated in semi-structured qualitative interviews to explore feasibility, acceptability, and barriers to telephone-delivered treatment in this context. Thematic coding analysis was conducted to identify key themes. Findings: Three major response themes emerged: 1) Advantages of telehealth delivery of CETA, 2) Disadvantages or barriers to telehealth delivery of CETA, 3) AYA recommendations for optimizing telehealth (ways to improve telehealth delivery in Zambia. Results indicate that logistical and sociocultural barriers i.e., providing AYA with phones to use for sessions, facilitating one face-to-face meeting with providers) need to be addressed for success of remotely delivered services. Conclusion: AYA in this sample reported telehealth delivery reduces some access barriers to engaging in mental health care provision in Zambia. Addressing logistical and sociocultural challenges identified in this study will optimize feasibility of telehealth delivery and will support the integration of virtual mental health services in the Zambian health system.